2020
DOI: 10.1128/aem.02749-19
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Produced by the Fast-Growing Marine Bacterium Vibrio natriegens through Heterologous Biosynthesis: Characterization and Application

Abstract: Melanin is a pigment produced by organisms throughout all domains of life. Due to its unique physicochemical properties, biocompatibility, and biostability, there has been an increasing interest in the use of melanin for broad applications. In the vast majority of studies, melanin has been either chemically synthesized or isolated from animals, which has restricted its use to small-scale applications. Using bacteria as biocatalysts is a promising and economical alternative for the large-scale production of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 50 publications
3
76
0
Order By: Relevance
“…in protecting mammalian cells from UV irradiation. Results revealed 90% survival rate of HeLa cells in melanized cell culture [ 128 ]. In another report, Bio lip balm made from crude pigment (extracted from S. bellus sp.…”
Section: Industrial and Therapeutic Applicationsmentioning
confidence: 99%
“…in protecting mammalian cells from UV irradiation. Results revealed 90% survival rate of HeLa cells in melanized cell culture [ 128 ]. In another report, Bio lip balm made from crude pigment (extracted from S. bellus sp.…”
Section: Industrial and Therapeutic Applicationsmentioning
confidence: 99%
“…[ 171–173 ] Melanins display paramagnetic character due to free radicals in their structures (e.g., semiquinone free radicals) which absorb microwaves under magnetic fields yielding spectra characteristic of the radical species present. EPR/ESR spectroscopy is therefore a potent method of studying melanins, with reports of its use for fundamental biochemistry studies (e.g., melanin type, [ 169,174–177 ] effect of pH [ 178–180 ] ), characterising melanins from different species including bacteria ( Rubrivivax benzoatilyticus JA2, [ 121 ] Vibrio natriegens , [ 181 ] Streptomyces cyaneofuscatus [ 182 ] ), yeast ( Cryptococcus neoformans [ 167 ] ), mushrooms ( Inonotus hispidus [ 183 ] ), black soldier flies ( Hermetia illucens [ 184,185 ] ), squid ( Loligo opalescens [ 175 ] ), cuttlefish ( Sepia officinalis [ 186 ] ), and cephalopod ink sacs from the Jurassic era. [ 187 ] Ionizing irradiation changes the EPR/ESR signals of fungal melanins due to changes in the electronic structure of the melanins, which informed a fascinating study of melanized fungal cells ( Wangiella dermatitidis , Cryptococcus Neoformans and Cladosporium Sphaerospermum ) which displayed increased growth relative to nonmelanized cells after exposure to ionizing radiation.…”
Section: Analysis Of Melaninsmentioning
confidence: 99%
“…[ 356–360 ] Static light scattering (SLS) observes the average scattering intensity of a solution/suspension over a period of time, whereas dynamic light scattering (DLS) observes fluctuations of the scattered light over very short periods of time, offering insights into molecular weights of polymers and particle sizes (typically nanometer scale and upward). Light scattering has been used to study synthetic melanins (e.g., polydopamine [ 361,362 ] ), naturally occurring melanins in bacteria ( Vibrio natriegens [ 181 ] ), yeast ( Cryptococcus neoformans [ 167 ] ), fungi ( Aspergillus oryzae [ 363 ] ), mushrooms ( Inonotus hispidus [ 183 ] ), cuttlefish ( Sepia officinalis [ 362 ] ), and can be used to study the health of eyes for patients with various conditions (e.g., for patients with pigmentary dispersion glaucoma [ 364 ] ).…”
Section: Analysis Of Melaninsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial Melanin is a product of biosynthesis of Ltyrosine via the enzyme tyrosinase oxidizing it into L-3, 4dihydroxyphenylalanine which is further metabolized into dopachrome and finally converted to melanin by oxidoreduction where the color usually ranges from black-brown in color (El-Naggar and El-Ewasy, 2017). Traditional melanin nanoparticle synthesis usually takes around 12 h, but Wang et al (2020) demonstrated the production of melanin nanoparticle synthesis in bacteria within 30 min by controlling the growth of cell-free conditions by changing the salinity concentration of the medium and incubation period. This demonstrates the exciting potential of bacteria as melanin pigment factories and melanin has a broad range of usages such as anti-oxidative, anti-cancer, anti-bacterial, anti-viral properties also displaying thermal resistance, radiation damage by absorption of wide range electromagnetic spectrum, and even chemical resistance (Narsing Rao et al, 2017).…”
Section: Melaninmentioning
confidence: 99%